Efeitos de dois tipos de pergunta sobre os comportamentos verbal e não-verbal - PAZ, Mariana Vargas (2007)
The present study intent to evaluate if the sinalization of changing on programmed contingencies through the presentation of question should turn the following of rules more probable to change when the contingencies modified. Twelve pre-grade students were exposed to a matching-to-sample procedure. The respondents pointed, sequentially, to three comparison stimuli in the presence of a sample stimuli. The presentation of correct sequencies produce points exchangeable for money. The responses were reinforced in CRF. The participants were distributed in four experimental conditions, each one consisted of four sessions. The session 1 was the base line. The programmed contingencies in Session 2 were changed in Session 3 and remained unchanged in Session 4. In Conditions 1 and 2, the nonverbal behavior was established through differential reinforcement and in Conditions 3 and 4 it was established through instructions. Two types of question were asked during the experiment: question Type 1 consisted in asking the participant to describe the behavior that produce reinforcement; and question Type 2 consisted in asking the participant to evaluate the possibility of exist or not more than one behavior that is reinforced in experimental situation. Question Type 1 was presented each three trials during the Sessions 2, 3 and 4 for all conditions; while question Type 2 was presented alternately in the beginning of Session 3 or Session 4. The results showed that two of three participants of Condition 1 and all of Condition 2 modified their verbal and nonverbal behaviors when the contingencies were changed. In Condition 3, all participants changed their behaviors when the contingencies changed and two of three modified their behaviors when the contingencies changed in Condition 4. This indicate that the question Type 2, join to the question Type 1, contributed to the presentation of verbal and nonverbal behaviors more sensitivity to the changing in contingencies when the nonverbal behavior was established through instructions. The results may aid in clarifying the role of questions in sensitivity of verbal and nonverbal behaviors to changing in contingencies.